Inferior Right Hepatic Vein: A Useful Anatomic Variation for Isolated Resection of Segment VIII - Klaus Steinbrück; Reinaldo Fernandes; Giuliano Bento; Rafael Vasconcelos; Gustavo Stoduto; Thomas Auel; Lúcio F. Pacheco-Moreira (Case Reports in Surgery)
Anatomical resection of segment VIII (SVIII) is one of the most difficult hepatectomies to perform. Although it is the best choice of surgical treatment for tumors located at SVIII, its feasibility can be compromised when the right hepatic vein (RHV) must be resected en bloc with SVIII. Herein we describe a case of a cirrhotic patient that was submitted to segmentectomy VIII in bloc with the main trunk of the RHV, due to hepatocellular carcinoma. The resection could only be performed because a well developed inferior right hepatic vein (IRHV) was present. Anatomical variations of the liver vascularization should be used by liver surgeons to improve surgical results.